Is there a green paradox? - Michael Hoel (Center for Economic Studies and ifo Institute (CESifo), 2010)
A sufficiently rapidly rising carbon tax may increase near-term emissions compared with the case of no carbon tax. Even so, such a carbon tax path may reduce total costs related to climate change, since the tax may reduce total carbon extraction. A government cannot commit to a specific carbon tax rate in the distant future. For reasonable assumptions about expectation formation, a higher present carbon tax will reduce near-term carbon emissions. Moreover, whatever the expectations about future tax rates are, near-term emissions will decline for a sufficiently high carbon tax. However, if the near-term tax rate for some reason is set below its optimal level, increased concern for the climate may change taxes in a manner that increases near-term emissions.
Keywords: Q31; Q38; Q41; Q48; Q54; Q58; 330; climate change; exhaustible resources; green paradox; carbon tax; Klimaschutz; Erschöpfbare Ressourcen; Ökosteuer; Kohlendioxid; Umweltpolitik; Theorie